Biography of world great women - Sumanlata (Cyber Tech Publications, 2013)
Introduction -- Joan of Arc -- Florence of Nightingale -- Mother Teresa -- Margaret Thatcher -- Anne Frank -- Megawati Sukarnoputri -- Catherine of Sienna -- Indira Gandhi -- Rosa Parks -- Gloria Macapagal-Arroyo -- Emmeline Pankhurst -- Hillary Rodham Clinton -- Catherine de' Medici -- Bibliography -- Index.